Development of a prioritisation tool for the updating of clinical guideline questions: the UpPriority Tool protocol. Issue 8 (3rd August 2017) - Martínez García, Laura; Pardo-Hernandez, Hector; Niño de Guzman, Ena; Superchi, Cecilia; Ballesteros, Monica; McFarlane, Emma; Penman, Katrina; Posso, Margarita; Roqué i Figuls, Marta; Sanabria, Andrea Juliana; Selva, Anna; Vernooij, Robin WM; et al.
Abstract : Introduction: Due to a continuous emergence of new evidence, clinical guidelines (CGs) require regular surveillance of evidence to maintain their trustworthiness. The updating of CGs is resource intensive and time consuming; therefore, updating may include a prioritisation process to efficiently ensure recommendations remain up to date. The objective of our project is to develop a pragmatic tool to prioritise clinical questions for updating within a CG. Methods and analysis: To develop the tool, we will use the results and conclusions of a systematic review of methodological research on prioritisation processes for updating and will adopt a methodological approach we have successfully implemented in a previous experience. We will perform a multistep process including (1) generation of an initial version of the tool, (2) optimisation of the tool (feasibility test of the tool, semistructured interviews, Delphi consensus survey, external review by CG methodologists and users and pilot test of the tool) and (3) approval of the final version of the tool. At each step of the process, we will (1) calculate absolute frequencies and proportions (quantitative data), (2) use content analysis to summarise and draw conclusions (qualitative data) and (3) draft a final report, discuss results and refine the previous versions of the tool. Finally, we will calculate intraclass coefficients with 95% CIs for each item and overall as indicators of agreement among reviewers. Ethics and dissemination: We have obtained a waiver of approval from the Clinical Research Ethics Committee at the Hospital de la Santa Creu i Sant Pau (Barcelona). The results of the study will be published in peer-reviewed journal and communicated to interested stakeholders. The tool could support the standardisation of prioritisation processes for updating CGs and therefore have important implications for a more efficient use of resources in the CG field.